ОЦЕНКИ КОНЕЧНОЙ ГАЗООТДАЧИ ТЕРРИГЕННЫХ ПРОДУКТИВНЫХ ПЛАСТОВ ПРИ ИСПОЛЬЗОВАНИИ ВЕРОЯТНОСТНО-СТАТИСТИЧЕСКИХ МЕТОДОВ (World Science, 2016)
The questions to assess the ultimate gas recovery clastic productive formations using probabilistic and statistical methods. Results projected gas recovery factors in their lithological structure and internal energy, which belongs to the main factors influencing the ultimate gas recovery